CRISPR: a revolutionary tool for modeling and treating cancer and Duchenne muscular dystrophy - Eva, Israt Ara Jannat (Brac University, 2023)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Pharmacy, 2022.